The Problem of Contextualizing a Prestigious Yet Non-Divine Jesus of Islamic Tradition: Theorizing a Radical Transition in the Course of Christology from the New Testament to the Qur’an - Syed M. Waqas (Ulumuna, 2021)
This article addresses the question of the messianic motif of Christianity making its way into the Qur’an without wearing a badge of high New Testament Christology. It attempts to explore and understand a potentially underlying connection among the Islamic ‘Isā, the New Testament Jesus, and the Jewish messiah in a quest for the configuration of a historical Christ through the ideological and historical minefields that exist between the Islamic and the Judeo-Christian Scriptures. The person of Jesus is, therefore, understood to be historical in the article without positing a response to the fundamental questions raised by the historical Jesus skepticism. What I will try to avoid in the following pages, on the contrary, is to treat and brand the Qur’anic portrayal of Jesus as a “stand-alone” concept—indifferent to the historical context of the Bible—hanging in a theological balance, as some critics would be inclined to call it. The article is linearly structured according to the major Qur’anic precepts and concepts developed around the person of Jesus through its text, which originally do not follow a particular sequence. A comparative study of Islamic Jesus against a two-pronged history of the concept is carried out for a critical analysis of the characterization of Islamic Jesus and the received concept of messiah. Such an analysis is important particularly on two fronts: comparison with the Judeo-Christian Bible and comparison with the orthodox Islamic position in certain aspects that fall outside the Qur’anic provenance. The life and ministry of Jesus pictured in the present article is, for the most part, a reconstruction of the important notion of Christology from within the Qur’an without breaking it down to a form of reductionism capitalizing on rudimentary borrowing from an external source.